Coronavirus outbreaks and its effects on the demand for electronic business in New Bussa, Niger state (Journal of Pure and Applied Sciences (Science Forum), 2026)
The outbreak of coronavirus which started from Wuhan in China and eventually cut across the borders of the countries into the world brought significant change to most aspects of human life. Drastic preventive measures that were put in place, such as social distances and lockdown, immediately brought effects and paved more way to the use of information technology especially in the area of business since man cannot do without his basic needs. This research aimed to study the use of e-business and social media platforms before and during the COVID-19 lockdown in the study area. Google Form was used for the self-constructed electronic business demand and adoption questionnaire and distributed online to WhatsApp contacts of the researchers involved in the study. The data were analyzed using charts, Pearson’s correlation statistics, paired sample, and independent sample t-test statistics. Considering the adoption of e-business platforms before and during coronavirus in the study area using different measuring factors, the result showed that even though there was higher demand for electronic business during the coronavirus outbreak in the study area, the higher demand was found to be insignificant and the respective factors were fully presented and discussed in the results.